2020
DOI: 10.1063/5.0008834
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic estimates of SARS-CoV-2 infection counts and their sensitivity to stochastic perturbation

Abstract: Despite the importance of having robust estimates of the time-asymptotic total number of infections, early estimates of COVID-19 show enormous fluctuations. Using COVID-19 data from different countries, we show that predictions are extremely sensitive to the reporting protocol and crucially depend on the last available data point before the maximum number of daily infections is reached. We propose a physical explanation for this sensitivity, using a susceptible-exposed-infected-recovered model, where the param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…Asadi et al (2020) analyzed COVID-19 cases in Spain using the Gompertz model and found a growth coefficient higher than the results of this study. Faranda et al (2020) studied COVID-19 data of different countries. They applied the Logistic model to the Chinese number of infections and it was observed that both growth coefficient and inflection point were more but R-square was greater than 0.99 in both researches.…”
Section: Model Selectionmentioning
confidence: 99%
“…Asadi et al (2020) analyzed COVID-19 cases in Spain using the Gompertz model and found a growth coefficient higher than the results of this study. Faranda et al (2020) studied COVID-19 data of different countries. They applied the Logistic model to the Chinese number of infections and it was observed that both growth coefficient and inflection point were more but R-square was greater than 0.99 in both researches.…”
Section: Model Selectionmentioning
confidence: 99%
“…These variations occur due to extrinsic factors, such as the availability of tests for essential screening, the natural history of the disease and changes in mitigation measures. Using an S-Shape curve model, Faranda et al 11 demonstrated the high sensitivity of the estimates to the last point of COVID-19 datasets. These authors provide a simulation study, replacing the last data point of the epidemic curves in the UK, France and Italy with a random number drawn from a uniform distribution, showing that the trajectory of the curves obtained under this process have a very high variability.…”
Section: /5mentioning
confidence: 99%
“…These authors provide a simulation study, replacing the last data point of the epidemic curves in the UK, France and Italy with a random number drawn from a uniform distribution, showing that the trajectory of the curves obtained under this process have a very high variability. Faranda et al 11 also showed that long-term forecasts and predictions based on more sophisticated models, such as the Susceptible-Exposed-Infected-Recovered (SEIR) compartmental model, are also extremely sensitive to biases in data collection and crucially depend on the last available data point.…”
mentioning
confidence: 99%
“…Furthermore, as Faranda et al indicated, early estimates of COVID-19 show enormous fluctuations, despite the importance of having robust estimates of the time-asymptotic total number of infections. 18 They showed that predictions are extremely sensitive to the reporting protocol and crucially depend on the last available data point before the maximum number of daily infections is reached.…”
Section: Figurementioning
confidence: 99%